2017
DOI: 10.1371/journal.pone.0169457
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma, Created at the Tip of an Elongated Flexible Capillary Using Low Electric Current, Can Slow the Progression of Melanoma

Abstract: IntroductionCold Atmospheric Plasma Jet (CAPJ), with ion temperature close to room temperature, has tremendous potential in biomedical engineering, and can potentially offer a therapeutic option that allows cancer cell elimination without damaging healthy tissue. We developed a hand-held flexible device for the delivery of CAPJ to the treatment site, with a modified high-frequency pulse generator operating at a RMS voltage of <1.2 kV and gas flow in the range 0.3–3 l/min. The aims of our study were to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
“…The unfortunate limitation in the use of CAP against tumors is that a high dose CAP exposure can also harm healthy mammalian cells [20], hence the need for precise micro devices. The recent focus in CAPanticancer treatment has thus been on developing small scale and high precision devices (micro capillaries), which led to successful inhibition of tumors [22,23].…”
mentioning
confidence: 99%
“…Besides the long‐lived species in the gas phase (nitrogen oxides, ozone, and hydrogen peroxides) and UV, the fluxes of charged particles (electrons, ions, and ion clusters), strong electric field and short‐lived neutral species (O, H, N, and OH) produced by direct plasma sources can interact with the object's surface directly. [ 15,30 ] However, the fluxes of charged particles and a strong electric field may trigger minor electric shocks, especially when the direct plasma sources are used to treat wounded tissues. Therefore, skin diseases with structural integrity, such as eczema, atopic dermatitis (AD), and so forth, are the appropriate object for using direct plasma sources.…”
Section: Cold Atmospheric Plasma Generationmentioning
confidence: 99%
“…The IVIS measurement also indicated that CAP treatment decreased the melanoma penetration into the epidermal layer by 48.2%. [ 30 ] This was a very important observation and was explained by a higher susceptibility to oxidative stress due to their increased metabolic activity, a stronger effect on cells in replication and high expression of aquaporins resulting in better uptake of ROS. [ 24 ]…”
Section: Applications In Dermatologymentioning
confidence: 99%
“…Great efforts are currently made extending the range of plasma applications with different devices. This includes blood coagulation [Amritkar et al, 2013;Aleinik et al, 2017;Miyamoto et al, 2017], ophthalmology [Rosani et al, 2015;Ye et al, 2015;Recek et al, 2016], oncology [Ye et al, 2015;Mirpour et al, 2016;Binenbaum et al, 2017], and various diseases in dermatology [Daeschlein et al, 2010[Daeschlein et al, , 2011Klebes et al, 2014]. Addressing not only the efficacy but also safety of different plasma sources or their optimum operational settings, genotoxic testing is indispensable.…”
Section: Introductionmentioning
confidence: 99%